2017
DOI: 10.1111/apm.12731
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium, an agent of reemerging sexually transmitted infections

Abstract: M. genitalium is a reemerging microorganism, responsible for sexually transmissible infections (STIs), with prevalence which varies depending on the country and population group studied. We report here M. genitalium prevalence among the specimens received for STI diagnosis in our routine microbiological laboratory in the university hospital in Marseille, France. We tested 4 624 samples from 3 793 patients using qPCR for M. genitalium, C. trachomatis, N. gonorrheae, T. pallidum. Of these samples, 528 (13.6%) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…1,13 Nevertheless, a number of prevalence studies worldwide have identified significant rates in both men and women. 6,13,2628 In the present study, the MG rate among women was 4.2%. Other Brazilian studies have reported rates from 0.9 to 28.1%.…”
Section: Discussionsupporting
confidence: 47%
“…1,13 Nevertheless, a number of prevalence studies worldwide have identified significant rates in both men and women. 6,13,2628 In the present study, the MG rate among women was 4.2%. Other Brazilian studies have reported rates from 0.9 to 28.1%.…”
Section: Discussionsupporting
confidence: 47%
“…The WHO has no global infection estimates and M. genitalium infection is not mandatory reported internationally (2,4). Nevertheless, numerous prevalence studies worldwide have identified rates between 1.3% and 3.9% in the general population (20)(21)(22). In the present study, prevalence of M. genitalium infection was 2.49%.…”
Section: Disscussionmentioning
confidence: 42%
“…Mycoplasma genitalium has successfully established itself as a relatively new sexually transmitted infectious (STI) agent that has devastating health effects on men and women alike [ 1 ]. The increasing prevalence of multidrug-resistant M. genitalium has made it the most common cause of STI, second to Chlamydia trachomatis [ 2 ]. A CDC report has recently put this bacteria on the “watch list” of antibiotic resistance threats, due to its rapid development of resistance to many antibiotics, including macrolides and fluoroquinolones used for treating other STIs [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%